2015
DOI: 10.1097/md.0000000000002022
|View full text |Cite
|
Sign up to set email alerts
|

Use of SSRI, But Not SNRI, Increased Upper and Lower Gastrointestinal Bleeding

Abstract: Selective serotonin receptor inhibitor (SSRI) and serotonin-noradrenaline reuptake inhibitor (SNRI) users have been reported to have an increased risk of upper gastrointestinal bleeding (UGIB), but their association with lower gastrointestinal bleeding (LGIB) is less studied. This study aimed to analyze the incidence of UGIB and LGIB among SSRI users, SNRI users, and controls.Using the National Health Insurance Research Database of Taiwan, 9753 subjects who were taking serotonin reuptake inhibitors (8809 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 33 publications
5
24
1
5
Order By: Relevance
“…Moreover, a high proportion (>45%) of our patients was taking gastroprotective agents, which may also affect the potential interactions. Similar findings were also reported in previous studies which did not report any significant interactions between SSRIs and other drugs …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, a high proportion (>45%) of our patients was taking gastroprotective agents, which may also affect the potential interactions. Similar findings were also reported in previous studies which did not report any significant interactions between SSRIs and other drugs …”
Section: Discussionsupporting
confidence: 92%
“…We also found that SNRIs and other antidepressants were not associated with the increased risk of UGIB, which was consistent with the study of Cheng et al The inclusion of these two control medications also addressed the concern that patients with depression may have a higher risk of peptic ulcer disease and hence the risk of UGIB rather than due to SSRIs use…”
Section: Discussionsupporting
confidence: 89%
“…The overall risks are substantially higher among individuals on concomitant use of nonsteroidal anti-inflammatory agents [127,128]. The association between the use of SNRIs and upper GI bleeding is less compelling with inconsistent results across studies [129,130,131]. The role of proton pump inhibitors against this increased risk of GI bleeding when used with SSRIs has not been firmly established [15,130,132,133].…”
Section: Bleedingmentioning
confidence: 99%
“…19 In contrast, a previous real-world study from Texas showed a smaller number of GI-bleeding events in patients taking NOAC than those receiving VKA; however, the number of patients treated with NOAC was small. [22][23][24][25][26][27][28] However, recent studies showed that a prestroke SSRI exposure was not associated with increased cerebral haemorrhage. 18,21 Conflicting results have been reported concerning the bleeding risk of patients receiving SSRI treatment in previous observational retrospective studies, which might be explained by different applied methodologies, health care system, selection bias, or follow-up periods.…”
Section: Resultsmentioning
confidence: 99%